Cloud atlas [videorecording (DVD)] - Tykwer, Tom, 1965-; Wachowski, Lilly, 1967-; Wachowski, Lana, 1965-; Hanks, Tom; Berry, Halle; Grant, Hugh; Weaving, Hugo, 1960-; Sarandon, Susan, 1946-; Mitchell, David (David Stephen) (Warner Home Video, 2013)
An exploration of how the actions of individual lives impact one another in the past, present and future, as one soul is shaped from a killer into a hero, and an act of kindness ripples across centuries to inspire a revolution. The story is a time-shifting weave of six interlinking narratives, with diverse settings from the savagery of a Pacific Island in the 1850s to a dystopian Korea of the near future.